Police Integrity Lost: Preliminary Findings of a National Study of Law Enforcement Officers Arrested - Stinson, Philip M (2013)
This presentation presents preliminary research findings of a study on the nature and extent of police crime in the United States. It provides information on the factors that influence how a law enforcement agency responds to arrests of its officers. The data indicate that civil rights litigation is a correlate of police misconduct